Ethnobotany of medicinal plants from Lampung Tribe around Way Kambas National Park, Indonesia - YUDIYANTO YUDIYANTO; NASRUL HAKIM; ANISATU Z. WAKHIDAH (Smujo International, 2022)
Abstract. Yudiyanto, Hakim N, Wakhidah AZ. 2022. Ethnobotany of medicinal plants from Lampung Tribe around Way Kambas National Park, Indonesia. Nusantara Bioscience 14: 84-94. The local communities of the Lampung Tribe around Way Kambas National Park (TNWK), Lampung, Indonesia, utilize forest resources through local community knowledge. However, cultural modernization can potentially lead to the erosion of people's traditional knowledge. Therefore, this study is essential to be conducted. This study aimed to inventory medicinal plant species and describe local communities' knowledge of the use of medicinal plants. Semi-structured interviews and observations collected ethnobotanical data. The results were presented in a table and diagram and then analyzed qualitatively. The results showed that the local community of the Lampung Tribe around the TNWK area used as many as 69 species of medicinal plants belonging to 39 families. Zingiberaceae was the family with the highest number of species. Leaves were the plant part that was used mainly by the local community. Boiling was the most widely used mode of preparation. The Lampung Tribe uses plants to treat various diseases grouped into external and internal diseases. The local community frequently experiences external diseases.